In Search of the Never-Never Mickey Dewar: Champion of History Across Many Genres - McGrath, Ann (ANU Press, 2019)
Mickey Dewar made a profound contribution to the history of the Northern Territory, which she performed across many genres. She produced high‑quality, memorable and multi-sensory histories, including the Cyclone Tracy exhibition at the Museum and Art Gallery of the Northern Territory and the reinterpretation of Fannie Bay Gaol. Informed by a great love of books, her passion for history was infectious. As well as offering three original chapters that appraise her work, this edited volume republishes her first book, In Search of the Never-Never. In Dewar's comprehensive and incisive appraisal of the literature of the Northern Territory, she provides brilliant, often amusing insights into the ever-changing representations of a region that has featured so large in the Australian popular imagination.